2015
DOI: 10.1111/jrh.12165
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Treatment and Outcomes Among Patients With AMI: Investigating Urban‐Rural Differences Among Hospitalized Patients

Abstract: Our findings suggest that despite limited access to cardiac care facilities, rural patients are accessing revascularization services. However, rural residents are more likely to undergo CABG during their index admission. High transfer rates suggest that rural regions rely on effective transfer networks to access invasive cardiac services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…However certain rural territories (clusters 3 and 4) with longer access times to the closest angiography facility had lower in-hospital prevalence and mortality for AMI, suggesting that longer distances to facilities are not systematically related to such health indicators. These results are consistent with a previous American study which concluded that in-hospital mortality for AMI was not related to a rural place of residence [ 40 ]. However, rural residents had a higher risk of transfer and 30-day readmission.…”
Section: Discussionsupporting
confidence: 93%
“…However certain rural territories (clusters 3 and 4) with longer access times to the closest angiography facility had lower in-hospital prevalence and mortality for AMI, suggesting that longer distances to facilities are not systematically related to such health indicators. These results are consistent with a previous American study which concluded that in-hospital mortality for AMI was not related to a rural place of residence [ 40 ]. However, rural residents had a higher risk of transfer and 30-day readmission.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple studies have detailed how rural patients experience delays or limitations in accessing health care (4, 35), and prior studies have examined the issue of patient choice in rural patients’ receipt of care in rural hospitals. (15, 21–23, 3639) Much of the data describing rural hospital bypass focuses on elective and scheduled health care (20, 24, 40), rather than unscheduled emergent care.…”
Section: Discussionmentioning
confidence: 99%
“…21 Several publications appeared following these classical studies, whose authors called attention to regional differences regarding the incidence and treatment of myocardial infarction. 13,[22][23][24][25][26][27][28][29] Furthermore, upon examining the same problem, several articles underlined the role of the social environment of the population. [30][31][32][33] In a meta-analysis of several studies, Manrique-Garcia et al 14 found that the incidence of myocardial infarction was influenced both by the social and economic status of the population as well as their educational background, that is the incidence of myocardial infarction was higher in underprivileged people.…”
Section: Discussionmentioning
confidence: 99%